PENGARUH PERCEIVED EASE OF USE DAN PERCEIVED USEFULNESS TERHADAP ACTUAL USE - Huda, Miftahul; Waluyowati, Nur Prima (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
The purpose of this research is to discover and analyze the technology acceptance model (TAM), namely the influence of Perceived Ease of Use and Perceived Usefulness of Actual Use Ticket Vending Machine of MRT Jakarta. TAM is a technology acceptance theory that explains and estimates user acceptance of an information system. The research object used was MRT Jakarta ticket vending machine users. This research classifies as explanatory research that describes the causal influence between dependent variable and independent variables using quantitative approach and data collection method performed by closed-distribution of questionnaire, incorporating the five-point Likert scale. Sampling was done using the purposive sampling method. This research uses 150 respondents as its sample that falls under the criteria of those that have used the MRT Jakarta’s ticket vending machine. Data is then processed and analyzed using the multiple linear regression analysis method with the aid of the 25th version of SPSS IBM Statistic data processing software. This research discovers that Perceived Ease of Use and Perceived Usefulness have significant impact on Actual Use MRT Jakarta Ticket Vending Machine.